Use of FEF25-75 in the Evaluation of Children with Bronchial Asthma at the University of Santo Tomas Hospital - Oloroso-Chavez, Kathleen; Gonzalez-Andaya, Agnes (Philippine Journal of Allergy, Asthma and Immunology, 2023)
Background: Retrospective studies have shown that asthmatic patients may have ventilatory defects in the presence of a normal FEV1. Thus, we conducted a prospective cross-sectional study to investigate on the utility of FEF25-75, in the context of having normal FEV1, in the evaluation of children with bronchial asthma at the University of Santo Tomas Hospital. Methodology: This is a cross-sectional study of 165 children aged 6 to 18 years diagnosed with bronchial asthma. All patients underwent routine assessment with a questionnaire, allergy skin prick test and spirometry. Results: Of the 165 asthmatic subjects, 116 (70.3%) had a normal FEV1. Of these, 103 (88.8%) had an additionally normal FEV1/FVC and FEF25-75. There were 3 subjects (2.6%) with normal FEV1 and FEF25-75 who also had low FEV1/FVC; 6 subjects (5.2%) had low FEF25-75 alone; and 4 subjects (3.4%) had both low FEV1/FVC and FEF25-75. A significant number of low FEV1/FVC group (67%) and low FEF25-75 group (50%) had exacerbations within the past 6 months necessitating steroid use. Subjects with low FEF25-75 (56.5 ± 8.26 %predicted) had significantly lower mean values even with normal FEV1 (88.17 ± 4.92) and FVC (92.5 ± 7.09). FEF25-75 is directly correlated with FEV1 (Spearman’s rho = 0.693, p<.001) and with FEV1/FVC (Spearman’s rho = 0.653, p<.001) among all children with bronchial asthma. Conclusion: FEF25-75 may be useful in the evaluation of children with bronchial asthma with normal FEV1. FEF25-75 is strongly and directly correlated to FEV1 and FEV1/FVC.